2012 IEEE International Symposium on Information Theory Proceedings 2012
DOI: 10.1109/isit.2012.6282286
|View full text |Cite
|
Sign up to set email alerts
|

Meeting the Levenshtein bound with equality by weighted-correlation complementary set

Abstract: Levenshtein improved the Welch bound on aperiodic correlation by weighting the cyclic shifts of the sequences over complex roots-of-unity. Although many works have been concerned on meeting the Welch bound with equality, no such effort has been reported for the Levenshtein bound. We show that the Levenshtein bound with equality is met if and only if the non-trivial aperiodic correlations have identical amplitude for all time-shifts, and the sequences form a novel class of complementary set whose aperiodic corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Recently, Liu, Guan and Mow have derived the generalized Levenshtein bound for quasi-complementary sequence sets [6] and shown that it is tighter than the corresponding Welch bound [2]. In addition, Liu and Guan have shown that the Levenshtein bound is met with equality by the weighted-correlation complementary sequences [7]. The readers are referred to [8]- [12] for more information on perfect-/quasi-complementary sequences.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Liu, Guan and Mow have derived the generalized Levenshtein bound for quasi-complementary sequence sets [6] and shown that it is tighter than the corresponding Welch bound [2]. In addition, Liu and Guan have shown that the Levenshtein bound is met with equality by the weighted-correlation complementary sequences [7]. The readers are referred to [8]- [12] for more information on perfect-/quasi-complementary sequences.…”
Section: Introductionmentioning
confidence: 99%
“…The idea of the Levenshtein bound is that the mean of the weighted aperiodic correlation squares for any sequence subset over the complex roots-of-unity is equal to or greater than that of the whole set which includes all the complex roots-of-unity sequences. In [5], Liu and Guan showed that the Levenshtein bound is met with equality by the weighted-correlation complementary sequences. In [6], Liu, Guan and Mow derived the generalized Levenshtein bound for quasi-complementary sequence set which is tighter than that of Welch [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, note that the previous cited interval does not include all the values of interest (see Figure 1 for instance). As explained in [11], an open question remains on the search for set of sequences that achieve the Levenshtein bound. At this point, a first partially negative answer can be given, thanks to Corollary 1.…”
Section: Improvement Over the Existing Boundsmentioning
confidence: 99%